Painting Pictures : Painting and media in the Digital Age. - Wolfsburg; Bobzin, Anne; Broeker, Holger; Dickel, Hans; Ebeling, Knut; Frost, Sarah; Jahn, Wolf; Lütgens, Annelie; Möntmann, Nina; Osswald, Anja; Reijnders, Frank; Schrader, Kristin; et al. (Bielefeld : Kerber Verlag Bielefeld, 2003)
Ackermann, Franz ; Aitken, Doug ; Calame, Ingrid ; Calvin, Brian ; Edwards, Ben ; Essenhigh, Inka ; Giehler, Torben ; Gursky, Andreas ; Havekost, Eberhard ; Hume, Gary ; Jones, Sarah ; Koons, Jeff ; Krisanamis, Udomsak ; Majerus, Michel ; Morris, Sarah ; Murakami, Takashi ; Oehlen, Albert ; Owens, Laura ; Parker, Erik ; Patterson, Richard ; Peyton, Elisabeth ; Pittman, Lari ; Prieto, Monique ; Rae, Fiona ; Raedecker, Michael ; Reed, David ; Ritchie, Matthew ; Ruyter, Lisa ; Scheibitz, Thomas ; Tillmans, Wolfgang ; Tomaselli, Fred ; Viola, Bill ; Vitali, Massimo ; Wall, Jeff
Exhibition. Painting Pictures : Painting and media in the Digital Age, Kunstmuseum Wolfsburg, Wolfsburg, 2003-03-01. 2003-06-29
boek